Some Aspects of legal Regulation of restricting the Rights and Freedoms of Police Officers - S. M. Bortnyk (Bulletin of Kharkiv National University of Internal Affairs)
The problem of restricting labor rights and freedoms, which is an important area of research for both domestic and foreign scholars, has been studied. International and national legislation on the establishment of restrictions on police officers while being recruited and during their service has been analyzed.